Poverty Persistence and Human Development: District-Level Evidence from Aceh - Syarifah Mursal Alawiyah; Aglis Anditha Hatmawan; Affandi (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study examines whether poverty exhibits persistent characteristics and whether human development is associated with lower poverty after accounting for historical poverty conditions in Aceh, Indonesia. Design/methodology/approach – The analysis uses balanced panel data from 23 districts and municipalities in Aceh during 2012–2023. Static and dynamic fixed-effects models are estimated, followed by robustness checks using dynamic two-way fixed effects and a lagged-HDI specification. Finding/Results – The baseline dynamic fixed-effects model provides consistent evidence of poverty persistence, with a lagged poverty coefficient of 0.6288. HDI is negatively associated with poverty in the baseline models. However, after year fixed effects and lagged HDI are introduced, the HDI coefficients remain negative but are no longer statistically significant. These results indicate that the evidence for poverty persistence is more robust than the evidence for a contemporaneous HDI effect. Originality/Value – The study integrates human development and poverty persistence within a district-level framework, showing that sustainable poverty reduction in Aceh requires attention to both human capability formation and the historical persistence of deprivation.